Arctic Oscillation responses to greenhouse warming and role of synoptic eddy feedback - Choi, DH; Kug, JS; Kwon, WT; Jin, FF; Baek, HJ; Min, SK (Journal of Geophysical Research, 2010)
This study investigates possible changes in the leading mode over the Northern Hemisphere, representing the Arctic Oscillation (AO), in response to the projected increases in greenhouse gas concentrations. This is performed by comparing present-day and future patterns simulated by a relatively high-resolution atmospheric general circulation model. It is demonstrated that the dipole pattern associated with the AO distinctively shifts poleward in the future climate. The poleward shift is more pronounced over the Pacific region than over the Atlantic region. This change in the AO pattern is consistent with the change in the synoptic eddy feedback, estimated from the divergence of the eddy-vorticity flux, indicating a close linkage between the AO change and the change in the synoptic eddy feedback. Further analysis of changes in eddy feedback strength suggests a possible hypothesis that the poleward shift of the jet stream and storm tracks can make synoptic eddy feedback more effective over the higher latitudes, which in turn enhances the poleward shift of the AO mode. X 1 1 13 scie scopus